ANALISIS PENGARUH APLIKASI TELEGRAM SEBAGAI MEDIA PEMBELAJARAN ALTERNATIF UNTUK MENINGKATKAN KEMAMPUAN KANJI DASAR - Adhellayani, - (2022)
The use of mobile learning during the Covid-19 pandemic is increasing because it is very helpful in conveying material during learning. Supported by the current era which is a native digital age, humans tend to be inseparable from gadgets. So the author intends to conduct research on the use of technology-based learning media. This study aims to analyze the effect of the Telegram application as a learning medium on efforts to improve the ability of basic kanji at the N5 level. The data sources of this study were the 12 participants of the Akari Kanji Course consisting of students, employees, housewives, and teachers. The theory used in this research is Gagne's IT-based learning media theory (1992) and the theory of mobile learning by Quinn Clark (2000). This study uses quantitative and qualitative research methods with data collection techniques using questionnaires, observations, interviews with Akari Kanji Course participants, and documentation. The data analysis technique used quantitative and qualitative analysis techniques (mixed methods). The results of quantitative data analysis showed that the results of the pretest and posttest did not produce a significant difference to student achievement. This is evidenced by the value of sig 2 tailed 0.077 ˃ 0.025 as a result of hypothesis testing. However, the results of the qualitative data analysis showed that the use of the Telegram application in learning basic kanji at the Akari Kanji Course resulted in a positive response from the participants. So it can be concluded that the use of the Telegram application as an alternative learning medium has a positive effect on the basic kanji abilities of the Akari Kanji Course participants. Further research, it is hoped that they can develop media by conducting experiments on the Telegram application in virtual meetings.